The Cormorant - Wendig, Chuck (Wendig, Chuck. Miriam Black series., 2014)
"Miriam is on the road again, having transitioned from "thief" to "killer". Hired by a wealthy businessman, she heads down to Florida to practice the one thing she's good at, but in her vision she sees him die by another's hand and on the wall written in blood is a message just for Miriam. She's expected"--P. [4] of cover.